Laemostenus (Iranosphodrus) rudichae, new subgenus and new species of Sphodrine beetle from Iran (Coleoptera: Carabidae: Sphodrini) - Lohaj, Roman (Acta entomologica slovenica (Ljubljana), 2011)
Laemostenus (Iranosphodrus subgen. nov.) rudichae sp. nov. from environs of the village Rayen (Iran, province Kerman) is described, illustrated and compared with the related subgenera and species of the genus Laemostenus Bonelli, 1810 (in the widest sense). Iranosphodrus new subgenus, apparently close to Pristonychus Dejean, 1828, is mainly characterised within the genus Laemostenus by the peculiar combination of several features, in particular theabsence of both anterior supraorbital setae of the head and the basolateralsetae of the pronotum, the toothed mesosternum in front of the mesocoxae, the presence of a prominent tooth on the anterior margin of the ventral side of the profemora, and the markedly curved mesotibiae in males. L.(I.) rudichae new species, besides the character state distinctive at subgeneric rank, is further characterized by the elongate, parallel sided, depigmented body, reduced eyes, and the structure of the aedeagus. The systematic position of the new taxon is discussed.
Keywords: Carabidae; Coleoptera; entomologija; entomology; favna; Iran; Laemostenus; new species; new subgenus; nove vrste; Sphodrina